Logos and Sophia (Philosophical-Theological lnterpretation) - Galuško, Viktor; Dainovič, Natalija (Respectus Philologicus, 2002)
In the article the ratio of the terms 'Logos' and 'Sophia' in the pre-Christian history and in the Gospel by John is esteemed.In the creations of the fathers of The Church the terms have received further development and obtained such characteristics, as - 'Logos is the person, alive face of the Christ'; 'Logos is not identified with the God by the Father and stands in eternally personal relation to the God, and to the Father'; 'it is the creator, a pattern, true God'; 'Logos is eternal'. The idea of Implementations of Logos makes the nature of John’s doctrine about Logos.
Keywords: -